A Godunov type method determining boundary conditions to predict the transient heat transfer in an expanding combustion chamber. Issue 12 (6th August 2019) - Hu, Chaobin; Zhang, Xiaobing
Abstract : Purpose: This paper aims to improve the reliability of numerical methods for predicting the transient heat transfers in combustion chambers heated internally by moving heat sources. Design/methodology/approach: A two-phase fluid dynamic model was used to govern the non-uniformly distributed moving heat sources. A Riemann-problem-based numerical scheme was provided to update the fluid field and provide convective boundary conditions for the heat transfer. The heat conduction in the solids was investigated by using a thermo-mechanical coupled model to obtain a reliable expanding velocity of the heat sources. The coupling between the combustion and the heat transfer is realized based on user subroutines VDFLUX and VUAMP in the commercial software ABAQUS. Findings: The capability of the numerical scheme in capturing discontinuities in initial conditions and source terms was validated by comparing the predicted results of commonly used verification cases with the corresponding analytical solutions. The coupled model and the numerical methods are capable of investigating heat transfer problems accompanied by extreme conditions such as transient effects, high-temperature and high-pressure working conditions. Originality/value: The work provides a reliable numerical method to obtain boundary conditions for predicting the heat transfers in solids heated by expanding multiphase reactive flows.